Efektivitas Pojok Pos Terhadap Peningkatan Penjualan UMKM pada PT Pos Indonesia (Persero) Kantor Cabang Binjai 20700 - Novy Arisca; Muhammad Irwan Padli Nasution (Badan Penerbit STIEPARI Press, 2023)
Micro, Small and Medium Enterprises (MSMEs) are an economic activity carried out by the majority of the Indonesian population as a way to earn income. Based on data released by the Ministry of Cooperatives and Small and Medium Enterprises in 2015, it is stated that the percentage of MSMEs in Indonesia is 90% and 10% are large businesses. MSMEs themselves have a very significant role in driving economic growth in Indonesia, namely 60%. In the regional economic sector, MSMEs also have an important role and have a positive impact on labor absorption and poverty alleviation. MSMEs have also proven capable of facing the global economic recession because MSMEs are not exposed to the global economy; producing goods in production and marketing; and MSMEs, are more adaptive and only require low costs. In Binjai City, MSMEs also have a role in providing employment opportunities and have an important role in the economic system. So every good party builds a special post corner to increase MSME sales. This research uses a special method to explain something in detail and this research was conducted at PT Pos Indonesia (Persero) Binjai Branch Office 20700.